Prospects of Biological Control of Green Ladybugs (Nezara viridula) Using Streptomyces spp. - Laksamana Agadhia Raharjo; Penta Suryaminarsih; Dita Megasari (Future Science, 2021)
Ecosystem damage due to the use of chemical pesticides increases every year, therefore alternative searches need to be known and developed. APH (Biological Control Agency) is a beneficial microbe that can control pest and disease populations. Streptomyces spp. Is a gram-positive soil bacterium that can be used against green ladybugs because Streptomyces spp. Able to produce chitinase enzymes that can break down chitin compounds in Exo – Skeleton Arthropod animals The purpose of this study was to determine the prospects for the use of Streptomyces spp. as APH of green shieldbugs.The description of this article includes: research results of Streptomyces spp., morphology, bio-ecology and bio-molecular green shieldbugs (Nezara viridula), as well as prospects for the use of Streptomyces spp. the results show that the use of Streptomyces spp. is able to control green ladybugs, because the chitinase enzyme produced can break down the chitin compound.The development of Streptomyces spp. has a lot of space, developments in the production of chitinase enzymes can be implemented and have clear potential.